Anhydride‐Assisted Spontaneous Room Temperature Sintering of Printed Bioresorbable Electronics. (2nd September 2019) - Li, Jiameng; Xu, Hang; Zhang, Zian; Hao, Yafeng; Wang, Hanjie; Huang, Xian
Abstract: Bioresorbable electronic devices are promising replacements for conventional build‐to‐last electronics in implantable biomedical systems and consumer electronics. However, bioresorbable devices are typically achieved by complex complementary metal oxide semiconductor fabrication processes that minimize exposure to humidity. Emerging printable techniques for bioresorbable electronics demand further improvement in electrical conductivity and mechanical robustness. This paper presents a room‐temperature spontaneous sintering method of bioresorbable inks that contain zinc nanoparticles and anhydride. The entire process can be conducted in atmosphere environment under 90% humidity within 300 min. It has minimum requirement for external heating and special ambient conditions, allowing humidity to trigger the surface chemistry of zinc nanoparticles and spontaneous welding between neighboring nanoparticles. The resulting bioresorbable patterns are highly conductive (σ = 72 400 S m −1 ) and mechanically robust (>1500 bending cycles) to enable practical applications. A radio circuit achieved through the above method can operate stably over 14 days in air and disappear in water for less than 30 min. The spontaneous room‐temperature sintering represents a rapid and energy‐efficient approach to achieve high‐performance bioresorbable electronics with improved mechanical robustness and electrical performance, leading to broader impacts in the areas of healthcare, information security, and consumer electronics. Abstract : A new spontaneous anhydride‐assisted sintering method at room temperature is presented here. Humidity is utilized to stimulate single‐step room‐temperature sintering of a unique bioresorbable ink based on zinc nanoparticles and anhydride to generate conductive matrixes with excellent conductivity and robustness of mechanical properties under minimum requirements for external heating and rigorous ambient conditions.